Hypothenemus hampei ferrari (coleoptera: curculionidae) answer to visual and olfative stimuli in field - de Souza, Rafael Assis; Pratissoli, Dirceu; de Araujo Junior, Luis Moreira; Pinheiro, Julia de Assis; Souza, Jean Francisco Vimercati; Madalon, Fernando Zanotti; Deolindo, Francieli Destefani; DAMASCENA, ALIXELHE PACHECO (Coffee Science - ISSN 1984-3909, 2020)
The coffee berry borer (CBB), Hypothenemus hampei (Ferrari, 1867) (Coleoptera: Curculionidae: Scolytinae) is one of the main pests of world coffee growing. For the purpose of monitoring the presence of this insect, colored traps and attractives have been developed. Then, the objective of this work was to determine the association between trap colors and ethanol: methanol proportions in the CBB catch, and also to determine the infestation in the coffee plantation by the H. hampei. Painted traps of red, green and colorful (red upper half + green lower half) and six volatile mixtures were used. The reference mixtures consisted of ethanol: methanol (E:M), in the proportions of 1:1 and 1:3, with addition of 0.002 and 0.004 kg of pure caffeine powder. The infestation in the coffee plantation was determined by the H. hampei number count into the fruits and the traps. The insects caught number showed significant interaction between the factors color and mixtures of volatile compounds (F107:85 = 2.46; p < 0.05). The peaks of H. hampei infestation occurred in the stages of grain formation (January) and maturation (April). The red traps with attractive E:M 1:1 + Benzoic Acid had the most significant effects in the H. hampei catch. Key words: Monitoring; pest; semiochemicals; volatile attractive.